Pengaruh Pendapatan Asli Daerah dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten Demak Jawa Tengah Tahun Anggaran 2021-2024 - Nurul Laily Nikmatus Sholihah; Khoirul Fuad; Mulyanto (Politeknik Raflesia Press, 2026)
This study analyzes the financial performance of Demak Regency for the period 2021–2024, which shows a positive but still fluctuating trend. Using a quantitative approach based on local government financial reports and analyzed through multiple linear regression with the help of SPSS, this study examines the effect of Local Own-Source Revenue (PAD) and capital expenditure on regional financial performance. Empirical results indicate that PAD has a positive and significant effect on financial performance, while capital expenditure does not show a significant effect. These findings emphasize the importance of strengthening the quality and achievement of PAD as well as controlling regional expenditure more optimally.